Struktur dan Fungsi Sosial Pantun dalam Acara Pernikahan Masyarakat Dusun Sekar Mengkuang Kecamatan Limbur Lubuk Mengkuang Kabupaten Bungo Provinsi Jambi - Lydia Febriani; Zulfadhli Zulfadhli (Persona: Kajian Bahasa dan Sastra, 2022)
Pantun can be used in various community activities, one of which is in weddings such as those carried out by the people of Sekar Mengkuang Hamlet, Bungo Regency, Jambi Province. The purpose of this study is to discuss the social structure and function of the rhyme in the wedding ceremony of the people of Sekar Mengkuang Hamlet, Limbur Lubuk Mengkuang District, Bungo Regency, Jambi Province. This research is included in literary-descriptive research, especially discussing folklore. The technique used in data collection is the technique of interview, observation, and documentation. Techniques for data analysis are the data identification stage, data classification, discussion and conclusion of the results of data analysis and reporting stages. The research findings include the structure of the rhyme in the wedding ceremony of the Sekar Mengkuang Hamlet, Bungo Regency, Jambi Province, namely (1) the physical structure in the form of diction, imagination, concrete words, figurative language, and verification, (2) the inner structure in the form of theme, taste, tone, and mandate. Then the social function of the rhyme in the wedding ceremony of the people of Sekar Mengkuang Hamlet, Bungo Regency, Jambi Province, namely entertaining, educating, passing on, identity and tradition.